PRAGMATICS OF JARGON, BARBARISMS AND EXOTIC WORDS IN TRANSLATED WORKS - Aliyorova Barno Toshtemirovna (Western European Studies, 2025)
In this article, translation pragmatics, slang, barbarism and exotic words in translation are unique lexical units and their use requires special attention in the translation process, these units create unique layers of meaning in the language and cultural, it is said to function as social or regional indicators
Keywords: semantic meaning; slang; translation pragmatics